Analisis Perkiraan Jumlah Produksi Tahu Menggunakan Metode Fuzzy Sugeno - Siti Nurdini; Gunadi Widi Nurcahyo; Julius Santony (Jurnal Sistim Informasi dan Teknologi, 2019)
Tofu industry XYZ is a small industry that is managed in the form of a home industry, where the process of estimating the amount to be produced is still manual. For that, a calculation process is needed that can be used to save or buy. Of the existing problems used in the Sugeno Fueno Method. In this method uses three variables, namely, demand variables, purchase variables and production variables. Each variable has three sets of Fuzzy, the demand variable consists of down, medium and up. Variables consist of few, medium and many. And the production variable consists of reduction, tolerable and increasing. From the results of the test data conducted by the Sugeno Method there is a difference of error of 2.148% means that the truth level is 97,852%. Determining this method can be applied to the tofu industry XYZ in estimating the amount of tofu production for the next period.